Sialic acid level is significantly elevated in IgM enriched protein fraction in sera of cancer patients. Issue 2 (4th March 2017) - Torii, Tsuyoshi; Kanemitsu, Kentaku; Hagiwara, Akeo
ABSTRACT: Serum sialic acid (SA) levels are important for diagnosis, follow-up, and mechanistic analysis of malignant diseases. However, little is known about the levels of SA bound to serum IgM. Here, we isolated IgM from sera of healthy individuals and patients with cancer using DEAE chromatography and 8% polyethylene glycol precipitation. In this fraction, which contained partially purified IgM (recovery; 52%; purity: 25%), SA was quantified with fluorescence detection-HPLC (detection limit: 0.08 μM). SA levels in the IgM-enriched fraction was significantly higher in cancer patients (104 ± 27 µM) than in healthy individuals (81 ± 11 µM; P = 0.003).